أثار الهجرة الغير شرعية للأفارقة علي الأمن الاقتصادي والاجتماعي الجزائري - بوراضي، لزهر; بوعليت، محمد Boualit, Mohamed (جامعة إبراهيم سلطان شيبوط الجزائر 3, 2021)
تعمل هذه الدراسة على البحث حول انعكاسات الهجرة غير الشرعية للأفارقة على مناطق العبور من خلال التعرض إلى أسبابها وأثارها على الجزائر التي تحولت في السنوات الأخيرة من مركز عبور إلى مركز استقرار لهم وما تحمله من تداعيات سياسية واقتصادية وأمنية عليها، والتحديات التي تفرضها هذه الظاهرة التي تتزايد كل يوم وتتعقد معها أثارها من خلال إيجاد آليات لمواجهتها من خلال النصوص القانونية التي تمنع الهجرة غير شرعية ويعاقب عليها القانون الجزائري بشكل واضح وصريح فالظاهرة تشكل عبئ على المجتمع وعلى الدولة من حيث اندماجهم واستقرارهم في المجتمع بشكل منظم رغم توفير الظروف إلا أنه يجود خلل كون الظاهرة في تزايد نظرا للظروف الموجودة في بلدانهم والجزائر بوابة لهم للعبور نحو أروبا تحديا أو الاستقرار بالجزائر وهذا شكل مشكلة من عدة جوانب. The present study aims to reveal the effects of illegal immigration of Africans on transit areas through the exposure of its causes and effects on Algeria, which in recent years has turned from a transit center to a stability for them and the social, economic and security repercussions, and the challenges that this phenomenon is posing are increasing every day and has complicated the effects left at all levels, forcing Algeria to find out mechanisms to confront it legally, through the texts that prohibit illegal immigration and which are punishable by the Algerian law in a clear and explicit way or those related to the security treatment, but it was unable to stop it, as this phenomenon has become a burden on the society and the state in terms of the integration and stability of illegal immigrants in society in an unorganized manner, and is constantly increasing due to the economic, social and security conditions in their countries, and the consideration of Algeria as a gateway for them to cross over to, or settle in, this led to the emergence of problems with multiple faces and dimensions.
Keywords: الهجرة غير الشرعية -- النصوص القانونية -- المسائلة القانونية -- الإستقرار المحلي -- الجزائر